Lithium nickel manganese oxide positive electrode material, preparation method thereof and electrochemical device
By doping metal elements into the Ni-Manganate Lithium Manganate positive electrode material and forming a phosphate coating layer, the structural distortion, capacity attenuation and gas production problems of the material during use are solved, and the stability and electrochemical performance of the material are improved.
Patent Information
- Application Number
- CN202411924689.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-21
AI Technical Summary
During the use of the Ni-Li-manganate cathode material, there are problems such as structural distortion, capacity attenuation, gas production and Coulomb efficiency, which limits its large-scale promotion.
By doping metal elements such as Ti, Zr, Al, Nb and Mo into the matrix material of the lithium nickel manganate positive electrode material, and forming a phosphate-containing cladding layer on the surface of the matrix material, the lattice structure, particle morphology and lithium ion conductivity of the material are improved.
The structural stability, charge and discharge rate, rate performance and circulation performance of nickel-manganese lithium co-electrode material are improved, and its circulation life is extended and gas production is reduced.
Smart Images

Figure CN119674053A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of new energy materials, and in particular to a lithium nickel manganese oxide positive electrode material, a preparation method thereof, and an electrochemical device. Background Art
[0002] With the rapid development of electric vehicles and portable electronic devices, the demand for lithium-ion batteries with high energy density and high power density is growing. Traditional cathode materials, such as LiCoO2 and LiNiMnCoO2, have been unable to meet the high energy density requirements due to their theoretical capacity and operating voltage limitations. Lithium nickel manganese oxide (LNMO) cathode materials have become an important choice for the next generation of high energy density lithium-ion batteries due to their advantages such as high output voltage, high energy density, low cost and environmental friendliness.
[0003] However, in practical applications, LNMO has problems such as structural distortion, capacity attenuation, gas production, and decreased coulombic efficiency during use, which limits the large-scale promotion of LNMO. Summary of the invention
[0004] In view of this, in order to solve at least one of the above technical problems, an embodiment of the present application provides a lithium nickel manganese oxide positive electrode material.
[0005] The embodiments of the present application also provide a method for preparing the aforementioned lithium nickel manganese oxide positive electrode material, and an electrochemical device using the lithium nickel manganese oxide positive electrode material.
[0006] In a first aspect, an embodiment of the present application provides a nickel manganese oxide positive electrode material, wherein the nickel manganese oxide positive electrode material comprises a base material and a coating layer located on the surface of the base material, wherein the base material has a general formula of Li(Li a Ni x Mn y M b O4), the M element includes at least one of Ti, Zr, Al, Nb and Mo, 0.02≤a≤0.06, 0.45≤x≤0.55, 1.4≤y≤1.6, 0.05≤b≤0.55, a+x+y+b=2, and the coating layer contains phosphate.
[0007] In some possible embodiments, the mass percentage of the M element in the lithium nickel manganese oxide positive electrode material is 0.05wt%-0.45wt%.
[0008] In some possible embodiments, the phosphate includes at least one of Li3PO4, AlPO4, Zr(HPO4)2, H3PO4 and NH4H2PO4.
[0009] In some possible embodiments, the mass percentage of the phosphate in the lithium nickel manganese oxide positive electrode material is 0.1 wt % to 0.5 wt %.
[0010] In some possible embodiments, the lithium nickel manganese oxide positive electrode material is a spinel structure.
[0011] In a second aspect, an embodiment of the present application provides a method for preparing a lithium nickel manganese oxide positive electrode material, comprising: A lithium nickel manganese oxide positive electrode material precursor, a lithium source and a dopant containing an M element are mixed to form a mixed material, and the mixed material is sintered once to obtain a matrix material. The general formula of the matrix material is Li(Li a Ni x Mn y M b O4), the M element includes at least one of Ti, Zr, Al, Nb and Mo, 0.02≤a≤0.06, 0.45≤x≤0.55, 1.4≤y≤1.6, 0.05≤b≤0.55, a+x+y+b=2; and The base material and the coating agent are mixed and subjected to secondary sintering to form a coating layer on the surface of the base material to obtain the lithium nickel manganese oxide positive electrode material, wherein the coating agent includes phosphate.
[0012] In some possible embodiments, the mass percentage of the M element in the dopant to the total mass of the lithium nickel manganese oxide positive electrode material precursor and the lithium source is 0.05wt%~1wt%.
[0013] In some possible embodiments, the coating agent includes at least one of Li3PO4, AlPO4, Zr(HPO4)2, H3PO4, and a mixture of NH4H2PO4 and Al(OH)3; and / or The mass percentage of the coating agent to the base material is 0.1wt%~0.5wt%.
[0014] In some possible embodiments, the primary sintering temperature is 850° C. to 1000° C., and the primary sintering time is 8 h to 15 h; and / or The temperature of the secondary sintering is 550° C. to 850° C., and the time of the secondary sintering is 7 h to 12 h.
[0015] In a third aspect, an embodiment of the present application provides an electrochemical device, which includes a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate includes a positive electrode active substance, and the positive electrode active substance is the aforementioned lithium nickel manganese oxide positive electrode material.
[0016] Compared with the prior art, the nickel manganese oxide positive electrode material provided in the embodiment of the present application is doped with metal elements such as Ti, Zr, Al, Nb and Mo in the base material. The above metal element doping can change the lattice structure of the base material, improve the roundness and uniformity of the particles, provide more channels for the diffusion of lithium ions, and improve Li + Diffusion rate. Moreover, the surface of the base material is also coated with a coating layer containing phosphate. Since phosphate has good lithium ion conductivity, it can promote the diffusion and migration of lithium ions in the lithium nickel manganese oxide positive electrode material, reduce the polarization of the electrode, and improve the charge and discharge efficiency and rate performance of the battery; at the same time, the phosphate coating layer can act as a physical barrier, effectively reducing the side reactions between the lithium nickel manganese oxide positive electrode material and the electrolyte, reducing the structural collapse and dissolution of active substances in the lithium nickel manganese oxide positive electrode material during the charge and discharge process, and reducing gas production, thereby improving the cycle life of the lithium nickel manganese oxide positive electrode material. The aforementioned elements are doped in the base material of the lithium nickel manganese oxide positive electrode material, and a coating layer containing phosphate is coated on the surface of the base material. The two cooperate with each other to synergistically improve the rate performance, cycle performance and service life of the lithium nickel manganese oxide positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 A process flow chart of a method for preparing a lithium nickel manganese oxide positive electrode material provided in one embodiment of the present application.
[0018] Figure 2 A schematic diagram of the structure of an electrochemical device provided in one embodiment of the present application.
[0019] Figure 3 This is a scanning electron microscope image of the lithium nickel manganese oxide positive electrode material in Example 1, Example 7 and Comparative Example 3 of the present application, wherein Figure 3 Figure (a) is a scanning electron microscope image of the lithium nickel manganese oxide positive electrode material in Comparative Example 3. Figure 3 Figure (b) is a scanning electron microscope image of the lithium nickel manganese oxide positive electrode material in Example 1. Figure 3 Figure (c) is a scanning electron microscope image of the lithium nickel manganese oxide positive electrode material in Example 7.
[0020] Figure 4 This is a comparison chart of the first cycle discharge capacity and first efficiency of the batteries prepared with the lithium nickel manganese oxide positive electrode materials in Examples 1-9 and Comparative Examples 1-3 of the present application.
[0021] Figure 5 This is a comparison chart of the high temperature cycle performance of batteries prepared with lithium nickel manganese oxide positive electrode materials in Examples 1-9 of the present application and Comparative Examples 1-3. DETAILED DESCRIPTION
[0022] The embodiments of the present application are described in detail below. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be understood as limiting the present application; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present application; in the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other; many specific details are elaborated in the following description to facilitate a full understanding of the present application, and the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0023] The present application provides a lithium nickel manganese oxide positive electrode material, which includes a base material and a coating layer located on the surface of the base material, wherein the base material has a general formula of Li(Li a Ni x Mn y M b O4), the M element includes at least one of Ti, Zr, Al, Nb and Mo, 0.02≤a≤0.06, 0.45≤x≤0.55, 1.4≤y≤1.6, 0.05≤b≤0.55, a+x+y+b=2, and the coating layer contains phosphate.
[0024] First, the base material of the lithium nickel manganese oxide positive electrode material is doped with M elements, and the M elements include at least one of Ti, Zr, Al, Nb and Mo. The above-mentioned M element doping can change the lattice structure of the nickel base material. The ions of the M elements will occupy the 16c vacancy of the base material octahedron, play a supporting role in the lattice, slow down the lattice volume change brought about by the charging and discharging process, enhance the structural stability of the lithium nickel manganese oxide positive electrode material, and make the crystal structure of the lithium nickel manganese oxide positive electrode material less likely to be distorted or collapsed during the cycle, thereby improving the stability and conductivity of the lithium nickel manganese oxide positive electrode material. At the same time, M element doping can also improve the morphology of the lithium nickel manganese oxide positive electrode material particles, improve the roundness and uniformity of the particles, provide more channels for the diffusion of lithium ions, and increase the diffusion rate of lithium ions, thereby improving the rate performance of the lithium nickel manganese oxide positive electrode material. The M elements can further include the three elements of Al, Ti and Nb, and the co-doping of these three elements can further improve the lattice structure of the lithium nickel manganese oxide positive electrode material.
[0025] In addition, a coating layer containing phosphate is formed on the surface of the base material of the lithium nickel manganese oxide positive electrode material. The phosphate has good lithium ion conductivity, which can promote the diffusion and migration of lithium ions in the lithium nickel manganese oxide positive electrode material, reduce electrode polarization, and improve the battery's charge and discharge efficiency and rate performance. At the same time, the coating layer can act as a physical barrier, effectively reducing the direct contact between the base material and the electrolyte, reducing the occurrence of side reactions and gas production, and during the charge and discharge process, it can reduce the structural collapse of the lithium nickel manganese oxide positive electrode material and the dissolution of active substances, slowing down the Jiang-Taylor effect, thereby improving the cycle life of the lithium nickel manganese oxide positive electrode material. In addition, the phosphate has good adhesion and is not easy to fall off from the surface of the base material, thereby ensuring the long-term protective effect of the coating layer.
[0026] Therefore, the positive electrode material in the embodiment of the present application can effectively improve the structural stability, charge and discharge rate, rate performance and cycle performance of the lithium nickel manganese oxide positive electrode material through the synergistic effect of M element doping and phosphate coating.
[0027] In some embodiments, the mass percentage of the M element in the lithium nickel manganese oxide positive electrode material can be 0.05wt%~0.45wt%. The moderate doping of the M element can improve the structural stability, thermal stability and rate performance of the lithium nickel manganese oxide positive electrode material without reducing the electrochemical properties of the lithium nickel manganese oxide positive electrode material, such as capacity. Exemplarily, it can be 0.05wt%, 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt% or any value within the numerical range composed of any two of the above values. The mass percentage of the M element in the lithium nickel manganese oxide positive electrode material can further be 0.1wt%~0.35wt%. When the content of the M element is high (0.35wt%~0.45wt%), part of the M element can form a metal oxide coating layer on the surface of the base material, further reducing the direct contact between the base material and the electrolyte.
[0028] In some embodiments, the phosphate may include at least one of Li3PO4, AlPO4, Zr(HPO4)2, H3PO4, and NH4H2PO4, etc. The above phosphates have high chemical stability and ionic conductivity, and can effectively further improve the interface stability, cycle performance, and rate performance of the lithium nickel manganese oxide positive electrode material.
[0029] In some embodiments, the mass percentage of phosphate in the lithium nickel manganese oxide positive electrode material can be 0.1wt%~0.5wt%, and the moderate coating of phosphate can balance the electrochemical performance of the lithium nickel manganese oxide positive electrode material and the stability of the coating layer. The phosphate content can be 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt% or any value within the numerical range composed of any two of the above values. The phosphate content can further be 0.25wt%~0.45wt%.
[0030] The nickel manganese oxide lithium positive electrode material has a spinel structure, has a high operating voltage and a unique three-dimensional lithium ion diffusion channel, can provide high energy density, excellent rate performance and long cycle life, and is suitable for batteries with high power requirements and long life.
[0031] In addition, the nickel manganese oxide lithium positive electrode material is a single crystal positive electrode material, and the formed single crystal particles have good roundness and uniformity. Compared with polycrystalline particles with grain boundaries, single crystal particles have a complete and orderly crystal structure, fewer lattice defects, and lower internal resistance, so they have higher structural stability and cycle performance.
[0032] In some embodiments, the particle size D50 of the lithium nickel manganese oxide positive electrode material may be 6 μm to 8 μm, and a smaller particle size is conducive to the rapid diffusion of lithium ions and the rapid transmission of electrons.
[0033] Compared with the prior art, the lithium nickel manganese oxide positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. By doping the above metal elements M in the matrix material, the lattice structure and particle morphology of the lithium nickel manganese oxide positive electrode material are improved, and the structural stability and rate performance of the lithium nickel manganese oxide positive electrode material are improved. Further controlling the doping amount of the M element in the lithium nickel manganese oxide positive electrode material is conducive to balancing the electrochemical properties and structural stability of the lithium nickel manganese oxide positive electrode material.
[0034] 3. By coating the surface of the base material with a coating layer containing phosphate, the lithium ion transmission rate of the lithium nickel manganese oxide positive electrode material can be increased, and the direct contact between the base material and the electrolyte can be reduced, thereby effectively improving the conductivity and cycle performance of the lithium nickel manganese oxide positive electrode material. By controlling the coating amount of phosphate in the lithium nickel manganese oxide positive electrode material, it is beneficial to further balance the electrochemical performance of the lithium nickel manganese oxide positive electrode material and the stability of the coating layer.
[0035] 3. The positive electrode material of lithium nickel manganese oxide can be a single crystal particle with a spinel structure. The spinel structure is beneficial to improving the energy density, rate performance and cycle life of the positive electrode material of lithium nickel manganese oxide; the single crystal structure has higher structural stability and cycle performance due to its complete crystal structure and low internal resistance.
[0036] Based on the same inventive concept, please refer to Figure 1 As shown, the present application embodiment provides a method for preparing a lithium nickel manganese oxide positive electrode material, which specifically includes the following steps: Step S1, mixing a lithium nickel manganese oxide positive electrode material precursor, a lithium source and a dopant containing an M element to form a mixed material, and sintering the mixed material once to obtain a matrix material, wherein the general formula of the matrix material is Li(Li a Ni x Mn y M b O4), the M element includes at least one of Ti, Zr, Al, Nb and Mo, 0.02≤a≤0.06, 0.45≤x≤0.55, 1.4≤y≤1.6, 0.05≤b≤0.55, a+x+y+b=2.
[0037] In this step, a matrix material of a lithium nickel manganese oxide positive electrode material doped with the M element is obtained by mixing a lithium nickel manganese oxide positive electrode material precursor, a lithium source and a dopant and sintering them once. The formed matrix material has a spinel phase, and the matrix material is a single crystal particle. Doping the M element into the bulk phase of the matrix material of the lithium nickel manganese oxide positive electrode material is beneficial to improving the lattice structure and particle morphology of the lithium nickel manganese oxide positive electrode material. Furthermore, the M element may include three elements, Al, Ti and Nb, and the co-doping of these three elements can further improve the lattice structure of the lithium nickel manganese oxide positive electrode material.
[0038] In some embodiments, the mixing method can be dry mixing, which can better evenly mix the dopant with the lithium nickel manganese oxide precursor and the lithium source without adding additional solvents or liquid adhesives, saving energy and costs, and being easy and efficient to operate, and is conducive to improving product purity. The mixing method can specifically include mixing, stirring or grinding with a high-speed mixer. It is understandable that the mixing method includes but is not limited to the above method.
[0039] In some embodiments, the dopant may include at least one of an oxide and a hydroxide corresponding to the M element.
[0040] In some embodiments, the mass percentage of the M element in the dopant to the total mass of the nickel manganese oxide lithium positive electrode material precursor and the lithium source can be 0.05wt%~1wt%, which is conducive to the appropriate introduction of the M element, and the doping effect is exerted without reducing the capacity. The mass percentage of the M element in the dopant to the total mass of the nickel manganese oxide lithium positive electrode material precursor and the lithium source can be 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, or any value within the range of any two of the above values. Further, the mass percentage of the M element in the dopant to the total mass of the nickel manganese oxide lithium positive electrode material precursor and the lithium source can be 0.05wt%~0.45wt%.
[0041] In some embodiments, the lithium source may include at least one of lithium carbonate, lithium hydroxide, and lithium nitrate.
[0042] In some embodiments, the general formula of the lithium nickel manganese oxide positive electrode material precursor is Ni c Mn d (OH)2, where 0.15≤c≤0.35, 0.65≤d≤0.85.
[0043] In some embodiments, the ratio of the molar number of lithium in the lithium source to the total molar number of transition metals in the lithium nickel manganese oxide positive electrode material precursor can be (1.0-1.15):1.
[0044] In the primary sintering process, materials are added to the crucible and sintered in a specific atmosphere, and then the materials are cooled and collected before being crushed to obtain the matrix material. The lithium nickel manganese oxide positive electrode material is prepared using a simple high-temperature solid phase method, and the most suitable sintering temperature and crucible feeding amount are determined to obtain a matrix material with higher electrochemical performance.
[0045] In some embodiments, the primary sintering temperature is 850°C to 1000°C. A higher primary sintering temperature can promote grain growth, reduce the number of grain boundaries and grain boundary defects, improve the crystallization quality and stability of the material, and facilitate the formation of a single crystal matrix material of a spinel phase. The primary sintering temperature can exemplarily be 850°C, 900°C, 950°C, 1000°C, or any value within the range of any two of the above values. Further, the primary sintering temperature can be 950°C to 1000°C.
[0046] The time of the primary sintering can be 8h~15h, which is conducive to fully sintering to form the matrix material. The time of the primary sintering can be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or any value within the range of any two of the above values. The time of the primary sintering can further be 10h~13h.
[0047] In some embodiments, the heating rate of the primary sintering may be 2° C. / min to 3° C. / min, which is beneficial for reducing crystal defects.
[0048] In some embodiments, the primary sintering atmosphere may be air atmosphere, oxygen-rich atmosphere or pure oxygen atmosphere, which is beneficial for the metal ions in the matrix material to maintain an oxidized state. The primary sintering atmosphere may further be pure oxygen atmosphere.
[0049] In some embodiments, the material can be added in batches during a single sintering, and the amount of material added to a single sintering device (such as a crucible) can be 1.5-3.0 kg / sintering device, illustratively, 1.5 kg / sintering device, 2.0 kg / sintering device, 2.5 kg / sintering device, or 3.0 kg / sintering device, etc. Controlling the amount of material added during sintering within the above range is conducive to the temperature rise of the material inside, as well as the normal entry and discharge of oxygen, thereby improving the uniformity of material sintering, while increasing the preparation speed, and reducing the excessive reaction of the first added material due to the slow process speed to produce by-products. Therefore, by adding materials in batches and controlling the amount of material added in a single time, the uniformity and efficiency of material sintering can be improved, while the crystal quality of the lithium nickel manganese oxide positive electrode material can be improved.
[0050] Step S2, mixing the base material and the coating agent and performing secondary sintering to form a coating layer on the surface of the base material to obtain a lithium nickel manganese oxide positive electrode material, wherein the coating agent includes phosphate.
[0051] Specifically, the obtained M element-doped matrix material is uniformly mixed with a coating agent, and then the mixture is subjected to secondary sintering, and then dispersed and sieved after cooling to obtain a lithium nickel manganese oxide positive electrode material doped with M element and coated with phosphate. First, phosphate can reduce the direct contact between the matrix material and the electrolyte on the surface of the matrix material, effectively reduce side reactions, and reduce the dissolution of transition metals in the matrix material. Secondly, phosphate can also increase the lithium ion transmission rate of the lithium nickel manganese oxide positive electrode material. In addition, phosphate has good adhesion and is not easy to fall off, thereby ensuring the long-term protective effect of the coating layer. Therefore, the presence of the phosphate coating layer further improves the structural stability and cycle performance of the lithium nickel manganese oxide positive electrode material.
[0052] In some embodiments, the coating agent may include at least one of Li3PO4, AlPO4, Zr(HPO4)2, H3PO4, and a mixture of NH4H2PO4 and Al(OH)3. The above coating agent has good chemical stability and ionic conductivity, and can further improve the structural stability and cycle performance of the lithium nickel manganese oxide positive electrode material.
[0053] In some embodiments, the mass percentage of the coating agent to the base material can be 0.1wt%~0.5wt%. Adding the coating agent according to the above ratio is conducive to adjusting the coating amount of the phosphate and balancing the performance improvement of the lithium nickel manganese oxide positive electrode material and the stability of the coating layer. Exemplarily, it can be 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt%, 0.5wt% or any value within the numerical range composed of any two of the above values. The mass percentage of the coating agent to the base material can further be 0.15wt%~0.35wt%.
[0054] In some embodiments, the method of mixing the matrix material and the coating agent can refer to the method of mixing the lithium nickel manganese oxide positive electrode material precursor, the lithium source and the dopant containing the M element in step S1.
[0055] During the secondary sintering process, materials can also be added through a crucible to prepare the lithium nickel manganese oxide positive electrode material using a simple high-temperature solid phase method. The material adding method and amount can refer to the primary sintering in step S1.
[0056] In some embodiments, the temperature of the secondary sintering is 550°C to 850°C. Within the above temperature range, the uniformity, compactness and bonding strength of the phosphate coating layer with the base material can be improved, and the phase change of the base material will not be caused, which is beneficial to improve the cycle stability and life of the lithium nickel manganese oxide positive electrode material without affecting the capacity and conductivity of the lithium nickel manganese oxide positive electrode material. The temperature of the secondary sintering can further be 600°C to 800°C, and can be 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C or any value within the range formed by any two of the above values.
[0057] The secondary sintering time can be 7h~12h, which is conducive to sufficient sintering to form the coating layer. The secondary sintering time can further be 9h~12h, and can be exemplarily 7h, 8h, 9h, 10h, 11h, 12h or any value within the range of any two of the above values.
[0058] In some embodiments, the heating rate of the secondary sintering may be 2° C. / min to 3° C. / min, which is beneficial for reducing crystal defects.
[0059] In some embodiments, the atmosphere of the secondary sintering can be air atmosphere, oxygen-rich atmosphere or pure oxygen atmosphere, which is conducive to maintaining the metal ions in the lithium nickel manganese oxide positive electrode material in an oxidized state. The atmosphere of the secondary sintering can further be pure oxygen atmosphere.
[0060] Compared with the prior art, the preparation method of the lithium nickel manganese oxide positive electrode material provided in the embodiment of the present application has the following beneficial effects: 1. By mixing the lithium nickel manganese oxide positive electrode material precursor with the dopant and performing a sintering, the M element is doped, the lattice structure and particle morphology of the lithium nickel manganese oxide positive electrode material are improved, and the structural stability and rate performance of the lithium nickel manganese oxide positive electrode material are improved.
[0061] 3. By coating with phosphate, the lithium ion transfer rate of the lithium nickel manganese oxide positive electrode material can be increased, and the direct contact between the matrix material and the electrolyte can be reduced, thereby effectively improving the conductivity and cycle performance of the lithium nickel manganese oxide positive electrode material.
[0062] 2. Further optimize the coating process, such as the temperature, time and atmosphere of the secondary sintering, to improve the coating effect, while improving the cycle stability and life of the lithium nickel manganese oxide positive electrode material without affecting the capacity and conductivity of the lithium nickel manganese oxide positive electrode material.
[0063] 4. The preparation method is simple and efficient, which is conducive to the large-scale production of lithium nickel manganese oxide positive electrode materials and has excellent commercial prospects.
[0064] See also Figure 2 As shown, an embodiment of the present application also provides an electrochemical device (such as a battery), wherein the electrochemical device 100 includes a positive electrode plate 10, a negative electrode plate 20, a separator 30 and an electrolyte 40, wherein the positive electrode plate 10 includes a positive electrode active material, and the positive electrode active material is the aforementioned lithium nickel manganese oxide positive electrode material.
[0065] The electrochemical device 100 prepared using the aforementioned lithium nickel manganese oxide positive electrode material has the advantages of high structural stability, high rate performance, high cycle stability and long life, and can be suitable for long-term cyclic use, meeting the requirements for high specific capacity, high power and long cycle life of the electrochemical device 100.
[0066] The above-mentioned lithium nickel manganese oxide positive electrode material and its preparation method and electrochemical device are further described below through specific examples.
[0067] Example 1 Step 1: Select the nickel manganese oxide cathode material precursor Ni 0.25 Mn 0.75(OH)2, add part of the lithium nickel manganese oxide positive electrode material precursor (about half of the total mass of the precursor), part of the lithium hydroxide (about half of the total mass of the lithium hydroxide) and dopants Al2O3, TiO2 and Nb2O5 into a high-speed mixer and mix evenly, and then add the remaining lithium nickel manganese oxide positive electrode material precursor and lithium hydroxide, wherein the ratio of the molar number of lithium in the total lithium source to the total molar number of transition metals in the total lithium nickel manganese oxide positive electrode material precursor is 1.05:1, and the doping amounts of Al2O3, TiO2 and Nb2O5 to the total mass of the lithium nickel manganese oxide positive electrode material precursor and the total lithium hydroxide are 0.2wt%, 0.15wt% and 0.35wt%, respectively.
[0068] The uniformly mixed mixture is added at a rate of 2.5 kg / crucible and sintered once in a pure oxygen atmosphere at a temperature of 950° C. for 10 h at a heating rate of 1.5° C. / min. The mixture is cooled and crushed to obtain a matrix material doped with the M element.
[0069] Step 2: Put the matrix material and the coating agent AlPO4 into a high-speed mixer and mix them evenly. The mass percentage of the added AlPO4 to the matrix material is 0.35wt%; add the evenly mixed mixture at a rate of 2.0kg / crucible and perform secondary sintering in a pure oxygen atmosphere at a temperature of 700°C for 10 hours. After cooling, disperse and sieve to obtain a lithium nickel manganese oxide positive electrode material.
[0070] Example 2 The difference from Example 1 is that in step S2, the mass percentage of AlPO4 added to the matrix material is 0.1wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0071] Example 3 The difference from Example 1 is that in step S2, the mass percentage of AlPO4 added to the matrix material is 0.5wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0072] Example 4 The difference from Example 1 is that in step S2, the coating agent is Li3PO4, and the mass percentage of the added Li3PO4 to the matrix material is 0.35wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0073] Example 5 The difference from Example 1 is that in step S2, the coating agent is Zr(HPO4)2, and the mass percentage of the added Zr(HPO4)2 to the base material is 0.35wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0074] Example 6 The difference from Example 1 is that in step S2, the coating agent is selected as a mixture of H3PO4 and Al(OH)3, and the mass percentage of the added H3PO4 and Al(OH)3 mixture to the base material is 0.35wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0075] Example 7 The difference from Example 1 is that in step S2, the temperature of the secondary sintering is 650° C. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0076] Example 8 The difference from Example 1 is that in step S1, the doping amounts of Al2O3, TiO2 and Nb2O5 in the total mass of the lithium nickel manganese oxide positive electrode material precursor and the total lithium hydroxide are 0.03wt%, 0.01wt% and 0.01wt% respectively, and the total doping amount is 0.05wt%. The other steps are basically the same as in Example 1, please refer to Example 1.
[0077] Example 9 The difference from Example 1 is that in step S1, the doping amounts of Al2O3, TiO2 and Nb2O5 in the total mass of the lithium nickel manganese oxide positive electrode material precursor and the total lithium hydroxide are 0.3wt%, 0.4wt% and 0.3wt% respectively, and the total doping amount is 1wt%. The other steps are basically the same as Example 1, please refer to Example 1.
[0078] Comparative Example 1 The difference from Example 1 is that no dopant is added in step S1, and no coating agent is added in step S2. The rest is basically the same as Example 1, please refer to Example 1.
[0079] Comparative Example 2 The difference from Example 1 is that in step S1, no dopant is added. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0080] Comparative Example 3 The difference from Example 1 is that in step S2, no coating agent is added. The other steps are basically the same as those in Example 1, please refer to Example 1.
[0081] The following tests were performed on the lithium nickel manganese oxide positive electrode materials obtained in Examples 1-9 and Comparative Examples 1-3.
[0082] Test method: 1. Scanning electron microscope (SEM) test: Auriga ChemiSEM scanning electron microscope was used for testing at an accelerating voltage of 10.00 kV, a working distance of 9.3~9.4 mm, and a magnification of 10,000×.
[0083] 2. Electrochemical performance test: Use button cells for electrical performance test, with a test voltage of 3.0V~5.0V; weigh the above-mentioned positive electrode materials, polyvinylidene fluoride (PVDF), and conductive agents (such as acetylene black or conductive carbon black) in a certain proportion, and add an appropriate amount of NMP to make a slurry. Then, evenly coat the slurry on aluminum foil, vacuum dry it at 115℃±5℃ / 8h, compact it, cut it into discs, and use metal lithium sheets as negative electrode materials. Finally, transfer them to the glove box and assemble them into CR2025 button cells. Use the LAND battery test system for constant current charge and discharge tests.
[0084] (I) Rate performance test: The test operating voltage range is 2.8V~4.4V, the temperature is 25℃, and the current density is 0.1C and 5C. The first discharge capacity and first efficiency of the battery made of nickel manganese oxide positive electrode material are measured.
[0085] (II) Cycle performance test: The operating voltage range is 3.0V~5.0V, the temperature is 45℃, and the current density is 1C for 100 cycles to measure the capacity retention rate of the battery made of nickel manganese oxide positive electrode material.
[0086] 3. Gas production test: Determine the amount of gas generated by a 2Ah soft-pack battery made of nickel manganese oxide positive electrode material when it is fully charged and stored in a 45°C environment for 7 days. The specific measurement method uses the immersion volume method and the solvent replacement method based on the Archimedes principle. This method can accurately obtain the amount of gas generated (mL) and calculate the gas generation per unit mass of positive electrode material in the positive electrode sheet (mL / g).
[0087] The relevant process parameters of Examples 1-9 and Comparative Examples 1-3 are shown in Table 1, and the corresponding test results of the obtained positive electrode materials and the prepared batteries are shown in Table 2.
[0088] The above results show: The lithium nickel manganese oxide positive electrode materials prepared in Example 1, Example 7 and Comparative Example 3 were observed by scanning electron microscope. Figure 3 , where the result of comparative example 3 is Figure 3 In Figure (a), the results of Example 1 are Figure 3 In Figure (b), the results of Example 7 are Figure 3 Figure (c) in Figure 1. Figure 3As shown in Figures (a) to (c) in the figure, the lithium nickel manganese oxide positive electrode material particles in Example 1, Example 7 and Comparative Example 3 all have a cross-sectional octahedral morphology, which is a single crystal particle morphology with good roundness and uniformity. Although Comparative Example 3 is not coated with phosphate, it is also doped with Al2O3, TiO2 and Nb2O5, which optimizes the crystal structure and has a single crystal particle morphology with good uniformity. At the same time, the roundness of the particles is also improved to a certain extent. Some small particles remain on the surface of Example 3 and Example 7, which are dot-shaped coating layers formed by phosphate.
[0089] Figure 4 These are the test results of the first discharge capacity and first efficiency of the batteries prepared with the lithium nickel manganese oxide positive electrode materials obtained in Examples 1-9 and Comparative Examples 1-3. Figure 5 The test results of the capacity retention rate of the battery prepared by the nickel manganese oxide lithium positive electrode material obtained in Examples 1-9 and Comparative Examples 1-3. Figure 4-5 Compared with Comparative Example 1, the electrochemical performance indicators of the batteries of the nickel manganese oxide positive electrode materials in Examples 1-9, such as the first discharge capacity at different rates, the relative size of the discharge capacity of 5C / 0.1C batteries, the cycle retention rate and the 3.80~4.3V capacity contribution, are all at a relatively high level. Among them, Example 1 is metal co-doped (0.2wt% Al2O3, 0.15wt% TiO2 and 0.35wt% Nb2O5), and is coated with 0.35wt% AlPO4 at the same time. The first cycle discharge capacity of the obtained nickel manganese oxide positive electrode material at 0.1C reaches 136.0mAh / g, and the first efficiency is 97.3%, which is improved compared with Comparative Examples 1-3. This is because the co-doping of metal ions can change the lattice structure of the nickel manganese oxide positive electrode material, while improving the roundness and uniformity of the particles, providing more channels for the diffusion of lithium ions, and improving Li + Diffusion rate. In addition, phosphate has good lithium ion conductivity, which can promote the diffusion and migration of lithium ions in the electrode material, reduce the polarization of the electrode, and improve the charge and discharge efficiency and rate performance of the battery; at the same time, the phosphate coating can act as a physical barrier to effectively reduce the side reactions between the nickel manganese oxide positive electrode material and the electrolyte, prevent the structural collapse of the nickel manganese oxide positive electrode material and the dissolution of active substances during the charge and discharge process, reduce gas production, and thus improve the cycle life of the nickel manganese oxide positive electrode material. In Example 3, due to the large amount of phosphate coating (0.5wt%), the first-cycle discharge capacity and first efficiency are reduced, but at high rate (5C) and long cycle (100 cycles), the performance is still better than that of Comparative Example 3.
[0090] As can be seen from Table 2, compared with Comparative Examples 1 and 3 without phosphate coating, the gas production of Examples 1-9 is lower. This is because the presence of the coating layer reduces the contact between the base material and the electrolyte, reduces side reactions, and thus reduces the gas production.
[0091] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A lithium nickel manganese oxide positive electrode material, characterized in that: It comprises a base material and a coating layer located on the surface of the base material, wherein the base material has a general formula of Li(Li a Ni x Mn y M b O4), the M element includes at least one of Ti, Zr, Al, Nb and Mo, 0.02≤a≤0.06, 0.45≤x≤0.55, 1.4≤y≤1.6, 0.05≤b≤0.55, a+x+y+b=2, and the coating layer contains phosphate.
2. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The mass percentage of the M element in the lithium nickel manganese oxide positive electrode material is 0.05wt%~0.45wt%.
3. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The phosphate includes at least one of Li3PO4, AlPO4, Zr(HPO4)2, H3PO4 and NH4H2PO4.
4. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The mass percentage of the phosphate in the lithium nickel manganese oxide positive electrode material is 0.1wt%-0.5wt%.
5. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that: The lithium nickel manganese oxide positive electrode material is a spinel structure.
6. A method for preparing a lithium nickel manganese oxide positive electrode material, characterized in that: include: A lithium nickel manganese oxide positive electrode material precursor, a lithium source and a dopant containing an M element are mixed to form a mixed material, and the mixed material is sintered once to obtain a matrix material. The general formula of the matrix material is Li(Li a Ni x Mn y M b O4), the M element includes at least one of Ti, Zr, Al, Nb and Mo, 0.02≤a≤0.06, 0.45≤x≤0.55, 1.4≤y≤1.6, 0.05≤b≤0.55, a+x+y+b=2; as well as The base material and the coating agent are mixed and subjected to secondary sintering to form a coating layer on the surface of the base material to obtain the lithium nickel manganese oxide positive electrode material, wherein the coating agent includes phosphate.
7. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 6, characterized in that: The mass percentage of the M element in the dopant to the total mass of the lithium nickel manganese oxide positive electrode material precursor and the lithium source is 0.05wt%~1wt%.
8. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 6, characterized in that: The coating agent includes at least one of Li3PO4, AlPO4, Zr(HPO4)2, H3PO4, and a mixture of NH4H2PO4 and Al(OH)3; and / or The mass percentage of the coating agent to the base material is 0.1wt%~0.5wt%.
9. The method for preparing a lithium nickel manganese oxide positive electrode material according to claim 6, characterized in that: The primary sintering temperature is 850°C to 1000°C, and the primary sintering time is 8h to 15h; and / or The temperature of the secondary sintering is 550° C. to 850° C., and the time of the secondary sintering is 7 h to 12 h.
10. An electrochemical device, characterized in that: The electrochemical device comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet comprises a positive electrode active material, and the positive electrode active material is a lithium nickel manganese oxide positive electrode material as described in any one of claims 1 to 5 or a lithium nickel manganese oxide positive electrode material prepared by the preparation method of the lithium nickel manganese oxide positive electrode material as described in any one of claims 6 to 9.
Citation Information
Cited By
Polyanionic positive electrode material as well as preparation method and application thereof
CN120497301A
Lithium nickel manganese oxide positive electrode material and preparation method thereof, positive electrode and lithium ion battery
CN120511292A
Lithium nickel manganese acid cathode material, preparation method thereof, cathode and lithium ion battery
CN120511292B
Preparation method of lithium nickel manganese oxide positive electrode active material, battery monomer, battery device and power utilization device
CN120809813A
Lithium nickel manganese oxide positive electrode material, preparation method thereof and electrochemical device
CN120933344A